The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3138/ptc.2015-72
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain: Current Patterns of Canadian Physiotherapy Service Delivery

Abstract: Purpose: The aim of this study was to describe the current patterns of service delivery of Canadian physiotherapy (PT) professionals working in adult musculoskeletal (MSK) outpatient practice. Methods: A total of 846 Canadian PT professionals working with an adult MSK outpatient clientele participated in an online survey about how they would treat a patient with low back pain (LBP). After reading an online clinical vignette about a fictional patient with varying insurance status, participants answered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In another vignette-based survey study of current PT practice patterns in LBP management, the authors identified that Canadian physiotherapists preferred to treat LBP patients two to three times per week, for 30 to 60 min per session, over a time period of one to three months [ 36 ]. These findings of Orozco and colleagues [ 36 ] are consistent with answers to the dose selection process of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another vignette-based survey study of current PT practice patterns in LBP management, the authors identified that Canadian physiotherapists preferred to treat LBP patients two to three times per week, for 30 to 60 min per session, over a time period of one to three months [ 36 ]. These findings of Orozco and colleagues [ 36 ] are consistent with answers to the dose selection process of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In another vignette-based survey study of current PT practice patterns in LBP management, the authors identified that Canadian physiotherapists preferred to treat LBP patients two to three times per week, for 30 to 60 min per session, over a time period of one to three months [ 36 ]. These findings of Orozco and colleagues [ 36 ] are consistent with answers to the dose selection process of our study. In comparison, a survey study conducted in New Zealand revealed that physiotherapists regularly provided between six to ten treatment sessions for NSCLBP patients and highlighted that this scope of therapy is not sufficient to support patients in self-managing their chronic conditions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study had other secondary objectives, which have been published elsewhere. 56 Study data were collected and managed using REDCap electronic data capture tools. 57…”
Section: Recruitment and Survey Distributionmentioning
confidence: 99%
“…Such guidelines should provide evidence-based benchmarks for service provision to ensure that all people receive services according to their clinical needs, moving professionals beyond the implicitly biased practices identified in the survey. 56 The creation of national guidelines would obviously require consensus among key stakeholders, such as third-party payers, professional associations, and government Health Ministry delegates. National guidelines would also need to be enacted within provincial contexts by professional boards and associations, and tangible incentives would likely need to be offered to clinics to ensure participation.…”
Section: Biases Regarding Low Back Painmentioning
confidence: 99%
“…While estimates of physical therapy patterns of care are available, these are either not specific to the workers' compensation sector or are from single Australian jurisdictions or outside Australia [13,14,[16][17][18][19][20][21]. Furthermore, the determinants of seeking physical therapy in compensated workers…”
Section: Introductionmentioning
confidence: 99%